Exploration of pathomechanism using comprehensive analysis of serum cytokines in polymyositis/dermatomyositis-interstitial lung disease. (18th July 2019) - Matsuda, Shogo; Kotani, Takuya; Ishida, Takaaki; Fukui, Keisuke; Fujiki, Youhei; Suzuka, Takayasu; Nagai, Koji; Hata, Kenichiro; Shoda, Takeshi; Isoda, Kentaro; Ito, Yuri; Makino, Shigeki; et al.
Abstract: Objectives: To elucidate the serum cytokine profile and address the pathomechanism of interstitial lung disease (ILD) complicated with PM/DM. Methods: Forty patients with PM/DM-ILD were enrolled, and principal components analysis and cluster analysis were performed to classify patients into subgroups. Additionally, we compared cytokine profiles between the survivors and dead patients and between anti-melanoma differentiation-associated gene 5 antibody- and anti-aminoacyl tRNA synthetase antibody-positive ILD patients. We also examined the association of various cytokines with disease activity indicators and prognosis of ILD. Results: The principal components analysis data allowed classification of the cytokine profile into three groups: group 1, neutrophilic and M1-macrophage-driven cytokines; group 2, type 1 Th cell-driven and M2-macrophage-induced cytokines; and group 3, M2-macrophage-driven cytokines. Cluster analysis showed the presence of PM/DM-ILD patient groups with high or low levels of total cytokines. Ninety percent of patients who died of ILD were included in clusters with high cytokine levels. Serum cytokine levels of all groups were significantly higher in the anti-melanoma differentiation-associated gene 5 antibody-positive patients than in the anti-aminoacyl tRNA synthetase antibody-positive patients. Groups 1 and 2 significantly correlated with known factors for poor prognosis, such as serum ferritin levels and alveolar-arterial oxygen difference. Serum cytokine levels of patients in group 1 were significantly higher initially and at 2 and 4 weeks in those who died. Conclusion: These findings suggested that the activation of monocytes, macrophages and type 1 Th cells, and neutrophils play roles in the pathomechanism of PM/DM-ILD, and group 1 cytokines could be useful biomarkers for predicting prognosis of PM/DM-ILD.